2016
DOI: 10.3390/en9100731
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of Hot Dry Rock Geothermal Resource in Daqing Oilfield, Northeast China

Abstract: Development and utilization of deep geothermal resources, especially a hot dry rock (HDR) geothermal resource, is beneficial for both economic and environmental consideration in oilfields. This study used data from multiple sources to assess the geothermal energy resource in the Daqing Oilfield. The temperature logs in boreholes (both shallow water wells and deep boreholes) and the drilling stem test temperature were used to create isothermal maps in depths. Upon the temperature field and thermophysical parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…These can also contribute to the high thermal state of the basement uplifts. According to the latest compilation of heat flow in the continental area of China (Jiang et al, 2016a(Jiang et al, , 2016b, in generally, the heat flow value has a decrease tendency from east to west basin which is accordance with the characteristics of the heat flow distribution in the back-arc basin, from east Bohai Bay basin: 68.9 mW/m 2 (the average heat flow value) to the middle Ordos basin: 61.6 mW/m 2 and the Western Junggar basin: 43.1 mW/m 2 , the Bohai Bay basin shows a high thermal state, which the average heat flow value is 68.9 mW/m 2 that is higher than the average heat flow value À61.5 mW/m 2 in mainland China and the Bohai Bay basin has a large range of heat flow value which ranges from 43.5 to 113.9 mW/m 2 , but they are mainly concentrated between 50 and 75 mW/m 2 , which may represent the regional thermal background. The Xiong'an New Area is located in the Jizhong depression, one tectonic unit of Bohai Bay basin, so Xiong'an New Area shows a higher thermal state , these values may be inaccurate, due to the lack of core samples and the influence of groundwater convection, but they can still reflect high background heat flow in Xiong'an New Area.…”
Section: Surface Heat Flow Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…These can also contribute to the high thermal state of the basement uplifts. According to the latest compilation of heat flow in the continental area of China (Jiang et al, 2016a(Jiang et al, , 2016b, in generally, the heat flow value has a decrease tendency from east to west basin which is accordance with the characteristics of the heat flow distribution in the back-arc basin, from east Bohai Bay basin: 68.9 mW/m 2 (the average heat flow value) to the middle Ordos basin: 61.6 mW/m 2 and the Western Junggar basin: 43.1 mW/m 2 , the Bohai Bay basin shows a high thermal state, which the average heat flow value is 68.9 mW/m 2 that is higher than the average heat flow value À61.5 mW/m 2 in mainland China and the Bohai Bay basin has a large range of heat flow value which ranges from 43.5 to 113.9 mW/m 2 , but they are mainly concentrated between 50 and 75 mW/m 2 , which may represent the regional thermal background. The Xiong'an New Area is located in the Jizhong depression, one tectonic unit of Bohai Bay basin, so Xiong'an New Area shows a higher thermal state , these values may be inaccurate, due to the lack of core samples and the influence of groundwater convection, but they can still reflect high background heat flow in Xiong'an New Area.…”
Section: Surface Heat Flow Distributionmentioning
confidence: 99%
“…The borehole temperature was measured by using a cable system consisting of a 42.9 mm diameter platinum sensor and a 5000 m long cable. This system has a sensitivity of 0.01 C and a precision of 0.1 C (Jiang et al, 2016a(Jiang et al, , 2016b. The platinum sensor was sent downward into each borehole at a slow rate of 7.6 m min À1 , in order to give it enough time to respond.…”
Section: Temperature Logsmentioning
confidence: 99%
“…Overall, in the Songliao Basin heat flow decreases toward basin margins (Wu and Xie, 1985). SK-II and Xushen1 are two boreholes in the Central Depression of Songliao Basin; the temperature data of SK-II were logged using the same system as we applied for this study, whereas the temperature data of Xushen1 were from Drill Stem Temperature Data (Jiang et al., 2016b). When comparing the temperature data from these two boreholes in the Central Depression and the data sets from the northwestern portion of Songliao Basin in this study (Table 3), it is clearly demonstrated that at similar depths, the two boreholes (HR1 and SPR1) in the northwestern portion of our study area show higher temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature gradients were calculated using the linear least squares regression method (Haenel et al., 1988; Powell et al., 1988) at depth intervals of 20 m for shallow wells, and 50 m for deep wells, respectively. To have a better constraint on the temperature field, 10 sets of drilling stem test data and the continuous temperature log of Well SK-2 from Jiang et al. (2016b) were used, with the location of these sites being on the west and northwest of our study area, though not shown on the map.…”
Section: Data Sourcementioning
confidence: 99%
“…Zeng et al analyzed the influencing factors of production performance of EGS at Yangbajing geothermal field, and found that main factors affecting the energy efficiency are the reservoir permeability, the water production rate and the injection temperature [19]. Jiang et al recently estimated the HDR geothermal resource in the Daqing Oilfield, Northeast China [20]. Li et al conducted a comparative analysis of power plant options for enhanced geothermal systems [21].…”
Section: Introductionmentioning
confidence: 99%